Impact of the internet on English language learning among university students: mediating role of academic self-efficacy - Wang, Ying; Yasmin, Fakhra; Akbar, Ahsan (Frontiers in Psychology, 2023)
The internet is a valuable resource in a technologically evolved society. The extant literature suggests that their scientific and educational usages are still limited. The current study asserts that the internet can provide new learning environments and opportunities for Chinese university students, hence increasing their motivation to learn. Particularly, the current study considers this to be the case for learning a foreign language (English), which leads to more efficient and effective language learning experiences, as well as more positive attitudes toward the efficiency of the internet for educational purposes. Purposive and convenience sampling techniques were employed to gather data from 15 public and private Chinese universities (406 students), those who are currently enrolled in English language courses. The analysis was performed using partial least squares-structural equation modeling (PLS-SEM) on smart PLS 4 software. Results revealed that student’s attitude toward the use of internet positively and significantly influence English language learning. Moreover, the mediating variable academic self-efficacy positively and significantly mediates the relationship between students’ attitude toward use of internet and English language learning. The current study recommends that students’ academic self-efficacy in learning a new language can be enhanced by giving them opportunities to learn internet skills. Further, students’ confidence in their academic abilities can be boosted using student-centered teaching strategies.